Irish public capital spending in a recession - Edgar Morgenroth (The Economic and Social Research Institute (ESRI), 2009)
In the past the first expenditure to be cut during an economic downturn was capital expenditure. However, the cuts in capital expenditure of the late 1980's and 90's had left Ireland with an infrastructure deficit. This note highlights a number of important issues, which should be considered before decisions to spend tax payer's money to support the construction sector are taken. Overall the paper concludes that in the context of a relatively high cost per job created via public investment, public capital projects should be undertaken on the basis that they have a long-run return to the whole economy.
Keywords: E6; H5; 330; public investment; construction sector; recession; Öffentliche Ausgaben; Infrastrukturinvestition; Bauwirtschaft; Konjunktur; Irland